EXPERIMENTAL VALIDATION OF A DYNAMIC MODEL FOR A RESIDENTIAL HEAT PUMP WITH IMMERSED CONDENSER - Nunes, R. O.; Faria, R. N.; Koury, R. N. N.; Machado, L.; Huebner, R. (Revista de Engenharia Térmica, 2015)
This work describes the validation of a dynamic model for a vapor compression residential heat pump with an immersed condenser. A detailed description of the modelling methodology for each component (compressor, capillary tube, evaporator, and immersed condenser) and the solution methodology employed in the complete heat pump system are presented. The main contribution of this work is in the dynamic modeling of the thermal processes occurring within the heat exchangers. Instabilities of the solutions for the heat exchangers are minimized by considering spatially and temporal varying errors. Another contribution of the model is the investigation of the temperature distribution inside the water storage tank, which highlights the possibility of using immersed condensers for this purpose without significant thermal stratification in the tank. Simulation results and experimental results are compared for transient operations using multivariate profiles of temperature, pressure and mass flow rates in heat exchangers during the water heating process.